Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for HLA Genotype and Use of Carbamazepine and Oxcarbazepine: 2017 Update - Phillips, Elizabeth J. (Clin Pharmacol Ther, 2018)
The variant allele HLA-B*15:02 is strongly associated with greater risk of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in patients treated with carbamazepine or oxcarbazepine. The variant allele HLA-A*31:01 is associated with greater risk of maculopapular exanthema, drug reaction with eosinophilia and systemic symptoms, and SJS/TEN in patients treated with carbamazepine. We summarize evidence from the published literature supporting these associations and provide recommendations for carbamazepine and oxcarbazepine use based on HLA genotypes.